2020
DOI: 10.1177/2325967119897423
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Proximal Anterior Cruciate Ligament Tears—Part 2: The Role of Internal Bracing on Gap Formation and Stabilization of Repair Techniques

Abstract: Background: The latest biomechanical studies on some form of internal bracing have shown improved stabilization for anterior cruciate ligament (ACL) repair, but gap formation and load-sharing function have not yet been reported. Hypothesis: Internal bracing of an adjustable ACL repair construct provides improved stabilization with reduced gap formation and higher residual loading on the ACL. Study Design: Controlled laboratory study. Methods: Internally braced ACL repair constructs with single– and double–cinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…Thus, it remains unclear whether these results can be reproduced for injuries due to non-winter sports injuries. (2) The mean age of the patients treated in our study is high, also in comparison to other studies on ACL repair using SA [ 12 , 13 , 40 ]. This is possibly due to the higher patient age in the ski region where this study was conducted.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, it remains unclear whether these results can be reproduced for injuries due to non-winter sports injuries. (2) The mean age of the patients treated in our study is high, also in comparison to other studies on ACL repair using SA [ 12 , 13 , 40 ]. This is possibly due to the higher patient age in the ski region where this study was conducted.…”
Section: Discussionsupporting
confidence: 51%
“… 26 The use of an ALD for primary ACL repair was tested in an experimental model compared to use of either a single cinch or double cinch suture, or the use of a suture anchor. 15 This recent study found the ALD with retensioning was superior to the other three techniques and led to significantly improved stabilization and reduced gap formation, along with the highest ultimate strength compared with the other tested techniques.…”
Section: Discussionmentioning
confidence: 90%
“…Correlating with these two published clinical papers on use of the IB was a recent biomechanical study which showed the benefit of adding an IB to either a single or double cinch type suture configuration for a primary repair relative to decreasing overall displacement and gap formation. 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present series there was no augmentation with suture nor scaffold due to the desire to optimize the favorable healing environment. However, some authors have suggested the use of an internal brace (IB) at the time of ACL repair to protect the biological environment and prevent displacement of the tissue in the healing phase by controlling anterior translation [ 13 , 21 , 25 , 26 ]. Other authors, in cases of delayed surgery, have promoted the use of biological scaffold or stimulation, especially when a shorter retracted stump is found, to optimize the healing environment between the torn ends of the ligament [ 27 ].…”
Section: Discussionmentioning
confidence: 99%